(untitled) (Bangladesh Medical Journal Khulna, 2017)
Kite flying is a popular sport in Indian subcontinent. The string or manjha, used for flying kites is coated with ground glass and glue, which makes it very sharp. This abrasive string can give rise to various types of injuries ranging from minor cuts to life threatening injuries and cause severe disabilities and death. The authors report a complicated case of cut throat injury due to kite string "manjha’ and its surgical management. Bang Med J (Khulna) 2016; 49 : 31-33